CONTRIBUTION OF CRISIS COUNSELLING AND DISASTER RESPONSE TO EFFECTIVE MANAGEMENT OF NATIONAL SECURITY EVENTS - JIBRIL, Nadikko B. (Journal of Professional Counselling, 2025)
National security events, including natural disasters, terrorist attacks, and civil unrest, pose significant challenges to societal stability. Effective crisis counselling and disaster response play a critical role in mitigating the psychological and social impact of such crises while ensuring swift recovery and national resilience. This paper examines the contribution of crisis counselling and disaster response strategies to effectively managing national security events. It highlights the psychological distress caused by crises and the necessity of immediate and longterm interventions through crisis counselling. By providing psychological first aid, traumainformed care, and resilience-building programs, crisis counselling helps affected individuals and communities cope with stress, fear, and post-traumatic disorders. Additionally, disaster response strategies, including emergency preparedness, coordination among security agencies, and community engagement, are essential in minimizing casualties and restoring normalcy. The study further explores the role of government agencies, non-governmental organizations, and mental health professionals in fostering effective disaster management and national security efforts. Findings suggest that integrating crisis counselling within national security frameworks enhances crisis preparedness, reduces long-term psychological effects, and promotes societal cohesion. The paper recommends increased investment in mental health services, improved coordination among response agencies, and public education on crisis preparedness. A comprehensive approach that combines psychological support with robust security measures ensures a more effective and sustainable response to national security events. Ultimately, addressing both the immediate and long-term consequences of crises strengthens national security, resilience, and recovery efforts.